Knee arthroplasty in the elderly - Aleksandra Modlińska; Karolina Cięszka; Pamela Świerczek; Klaudia Kwiatkowska; Karolina Kubiak; Marlena Kontowicz; Martyna Lamtych; Hanna Bednarek; Adrian Zwolinski; Olga Rymarska; Łukasz Neumann; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Background: One of the many problems related to geriatric patients are degenerative changes in joints. In this article authors discuss about the knee joint endoprosthesis. During preparations of this publishment special attention was paid to the following aspects: role and the meaning of preventing actions, explanation the clue and main goal of the surgery intervention, and it's simplified course. Subsequently there are short description of the knee joint with its most relevant to the fallowing subject structures. Furthermore the quantity of respective surgical procedure was given to approximate the scale of subject. Next paragraphs explaining why endoprothesis is the best way for dealing with this kind of problems, and the significance of the physiotherapist in whole process both before, and after surgery. Materials and methods: Analysis of available literature and articles in PubMed, ResearchGate and other scientific platforms related to discussed subject, using words: geriatrics, endoprothesis, knee arthroplasty, knee joint. Results: Gonarthrosis is a significant social problem. Endoprosthesis plastic surgery is performed on those patients who struggle badly in activities of daily living because of advanced articulations disorders. The main diagnoses underlying the primary knee replacement were primary bilateral gonarthrosis and other primary gonarthrosis accounted. The analysis of sources devoted to these issues includes people after 65 years old (mostly women) which occurs a low level of physical activity, the burden of metabolic disease such as diabetes (type 2). Authors demonstrated a correlation between excessive body weight, and insufficient production of synovial fluid, it's damage and in the final phase lost which is a direct reason for pain. The following thesis was proven based on the source material: thanks to arthroplasty the patients quality of life as improved by around 90 percent. When the physiotherapist is involved in the whole process, both in the pre- and post-surgery phase it is possible to obtain much better therapeutic effects. Conclusions: Knee arthroplasty can help restore independence to patients in their daily activities. The introduction of artificial foreign bodies into the pond to replace the damaged leads to an improvement in the quality of life of sick patients. The introduction of intensive rehabilitation, patient education and pharmacological treatment after arthroplasty allows for reduction of pain and faster recovery. There are many types of rehabilitation after knee replacement surgery, so the therapy plan has to be adapted to the individual patient.